Accounting restatements and audit quality in China. Issue 1 (June 2015) - Jiang, Haiyan; Habib, Ahsan; Zhou, Donghua
Abstract This paper examines the effect of audit quality on accounting restatements in China. Evidence on the determinants and consequences of accounting restatements in emerging markets is scant, although these countries are more vulnerable to financial report manipulation and subsequent restatements. For accounting restatement analysis we regress non-cash flow restatement observations and cash flow restatement observations on audit quality and restatement–audit quality interaction variables. Earnings manipulation increases the likelihood of non-cash flow restatement observations, but high quality audit constrains this effect. However, no such evidence is found for cash flow restatements.